Comparative Analysis of User Experience with the Agoda and Traveloka Applications Among University Students using the User Experience Questionnaire (UEQ) Method - Tessa Arianvira; Apriansyah Putra; Mira Afrina; Pacu Putra (Universitas Islam Indragiri, 2026)
Online Travel Agent (OTA) applications have become increasingly popular in supporting digital travel services; however, the quality of the user experience may vary across different applications. This study aims to compare the user experience of the Agoda and Traveloka applications among university students using the User Experience Questionnaire (UEQ) and to examine the influence of the six UEQ dimensions on user satisfaction using SmartPLS. A quantitative research approach was employed using purposive sampling among students at Universitas Sriwijaya. The primary dataset consisted of 100 evaluations from Agoda users and 100 evaluations from Traveloka users, following a pilot test involving 30 participants. The results of the UEQ benchmark comparison indicate that Traveloka outperformed Agoda in the dimensions of Attractiveness, Stimulation, and Novelty, whereas Agoda achieved higher scores in Perspicuity, Efficiency, and Dependability. A statistically significant difference between the two applications was identified only for the Stimulation dimension (p = 0.026). The SmartPLS analysis, conducted after indicator elimination, produced R² values of 0.207 for Agoda and 0.374 for Traveloka. For the Traveloka model, Stimulation was found to have a positive and significant effect on user satisfaction (t = 2.166, p = 0.030), whereas none of the structural paths in the Agoda model were statistically significant. These findings suggest that Traveloka provides a more engaging and motivating user experience than Agoda. Nevertheless, both applications require further improvement in their pragmatic quality dimensions, as indicated by the UEQ benchmark results.